First record of the Red Sea Mantis shrimp Erugosquilla massavensis (Kossmann, 1880) in the Greek Ionian Sea - Dimitriadis, Charalampos (Array, 2019)
The presence of the Red Sea Mantis shrimp Erugosquilla massavensis (Kossmann, 1880) is here reported for the first time from the southeastern Ionian Sea (Zakynthos Island, Greece). This record is the first evidence of the presence of a Lessepsian migrant crustacean in the aforementioned area while it fills the gap in the ongoing westward and northward distribution range expansion of this wide spread invader of the Mediterranean basin.